(3HdhZ GdCQH aj Yde GdCOHs - (3GdeGQhfj, GdoerWQGf narQMGJ, LHQGFjd Hf aQMGJ, (B1145 (3g`s ((3LHQGFjd Hf hgHI Gddg UObI GdWQGHdSjs)
(3ChdgG (B:s
(3Gddge jG ef NdbJ GdEfSGf hYdeJg GdHjGfhSejJg HdhZ GdCQH aj Yde GdCOHGdHGH GdChd ajeG LGA ef CfhGY GdLfGSGJ HGdJaUjd eY EjQGO GdThGgO IGdJeKjds
(3BNQgG (B:s
(3HeLGeY GdbdhH GdeSJhdj Ydi bhi GdfahS djWhd HPdc HGYg hjMSf GNJQGYgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 109s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdCOHs